1986
DOI: 10.1113/jphysiol.1986.sp016318
|View full text |Cite
|
Sign up to set email alerts
|

Amygdaloid influences on brain‐stem neurones in the rabbit.

Abstract: SUMMARY1. Electrical stimulation of the central nucleus of the amygdala in the urethane or a-chloralose anaesthetized rabbit evokes a bradyeardia with a rapid onset and a concomitant fall in arterial blood pressure.2. Extracellular neuronal activity was recorded in the ipsilateral nucleus tractus solitarius and dorsal vagal nucleus whilst stimulating the ipsilateral central nucleus of the amygdala, the aortic and vagus nerves.3. A total of 213 neurones were activated by stimulation of at least one of these inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…12). Similar facilitatory interactions have been observed in the absence of GABAA receptor antagonists in the rabbit when the CEN was stimulated (Cox, Jordan, Moruzzi, Schwaber, Spyer & Turner, 1985;see Fig. 14) and these observations correlated well with the fact that CEN activation in the conscious rabbit evokes a 'playing dead' response that includes bradyeardia and systemic hypotension (Applegate, Kapp, Underwood & McNall, 1983).…”
Section: Descending Control Of Cardiovascular Functionsupporting
confidence: 79%
“…12). Similar facilitatory interactions have been observed in the absence of GABAA receptor antagonists in the rabbit when the CEN was stimulated (Cox, Jordan, Moruzzi, Schwaber, Spyer & Turner, 1985;see Fig. 14) and these observations correlated well with the fact that CEN activation in the conscious rabbit evokes a 'playing dead' response that includes bradyeardia and systemic hypotension (Applegate, Kapp, Underwood & McNall, 1983).…”
Section: Descending Control Of Cardiovascular Functionsupporting
confidence: 79%
“…In contrast, in the rabbit on stimulating within the central nucleus of the amygdala, which is involved in the expression of affective behaviour, a facilitatory interaction between the effects of such stimulation and baroreceptor inputs has been demonstrated (see Pascoe, Bradley & Spyer, 1987). In this species the appropriate convergence of excitatory input has been observed in neurones of the NTS (Cox et al 1986). The behavioural response in the rabbit involves a marked bradycardia as part of a 'playing-dead' (Applegate, Kapp, Underwood & McNall, 1983) response unlike the defence response of the cat (Timms, 1981).…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, in a double-labelling study in the rabbit Higgins & Schwaber (1981) showed that the descending c.n. projection to the nucleus tractus solitarius overlapped the region of termination of aortic baroreceptor afferents and recent electrophysiological evidence (Cox, Jordan, Moruzzi, Schwaber, Spyer & Turner, 1986) has demonstrated that baroreceptor-sensitive neurones in the rabbit nucleus tractus solitarius and dorsal vagal nucleus can be influenced by stimulation of the c.n. This work was supported by grants from the Medical Research Council.…”
mentioning
confidence: 81%